Effects of a 12-Week Very-Low Carbohydrate High-Fat Diet on Maximal Aerobic Capacity, High-Intensity Intermittent Exercise, and Cardiac Autonomic Regulation: Non-randomized Parallel-Group Study - Dostal, Tomas; Plews, Daniel J.; Hofmann, Peter; Laursen, Paul B.; Cipryan, Lukas (Frontiers in Physiology, 2019)
Purpose: The aim of this non-randomized parallel group study was to examine the 12-week effects of a very low-carbohydrate high-fat diet (VLCHF) on maximal cardiorespiratory capacity, high-intensity interval training (HIIT) performance and cardiac autonomic regulation. Methods: Twenty-four recreationally trained participants allocated to either a VLCHF (N=12) or a habitual diet (HD; N=12) group completed 12 weeks of a diet and exercise (VLCHF) or an exercise only intervention (HD). Maximal graded exercise tests (GXT) were performed at baseline, after 4, 8 and 12 weeks. A supervised HIIT session and the 30-15 Intermittent Fitness Test (30-15IFT) were conducted once a week. Results: Total time to exhaustion (TTE) in both GXT and 30-15IFT largely increased in both VLCHF (p = 0.005, BF10 = 11.30 and p = <0.001, BF10 = >100, respectively) and HD (p = 0.018, BF10 = 3.87 and p = <0.001, BF10 = >100, respectively) groups after 12 weeks. Absolute maximal oxygen uptake (V ̇O2max) was not changed in both groups but relative V ̇O2max increased in VLCHF in concert with reductions body mass (66.7±10.2 to 63.1±8.5 kg). Cardiac autonomic regulation did not reveal any between-group differences after 12 weeks. VLCHF diet induced an increase in β-hydroxybutyrate, which tended to normalize during the intervention period. Conclusions: The 12-week VLCHF diet did not impair high-intensity continuous or intermittent exercise lasting up to 25 min, nor did it impair maximal cardiorespiratory performance or autonomic nervous system activity.